The Effect of Inflation, Rupiah Exchange Rate, Composite Stock Price Index, and BI Rate on Sharia Commercial Bank Liquidity in Indonesia - Rinda Quratul A'yun (Department of Islamic Economics, Postgraduate Program, UIN Kiai Haji Achmad Siddiq, Indonesia, 2024)
This study aims to analyze the influence of macroeconomic variables, including inflation, the rupiah exchange rate, the composite stock price index (IHSG), and Bank Indonesia’s benchmark interest rate (BI Rate), on the liquidity of Islamic commercial banks in Indonesia, as measured by the Financing to Deposit Ratio (FDR) during the period 2013–2018. Secondary data were obtained from banking financial reports, Bank Indonesia, the Financial Services Authority (OJK), and the Central Statistics Agency (BPS). The analytical method used was multiple linear regression with a quantitative approach. The results of the study indicate that the four independent variables simultaneously have a significant effect on the FDR of Islamic commercial banks. Partially, inflation and the rupiah exchange rate have a significant effect on the FDR, while the IHSG and BI Rate show no significant influence. These findings affirm that macroeconomic stability plays a crucial role in maintaining the liquidity health of Islamic banking. This research provides important implications for regulators and stakeholders in the Islamic banking industry in formulating monetary policies and liquidity management strategies.